Use of Distal Medial Sural Vessels as Recipient Vessels in Free Tissue Transfer - Smith, Mark L.; Molina, Bianca J.; Dayan, Erez; Kim, Julie N.; Kagen, Alexander; Dayan, Joseph H. (Journal of Reconstructive Microsurgery, 2017)
Background The medial sural vessels have been used extensively as donor vessels in free tissue transfer; however, there is sparse literature detailing their use as recipient vessels. The few existing reports involve small numbers of patients and describe operative approaches that are unnecessarily cumbersome. We explored our experience in free tissue transfer to the medial sural vessels and share a simplified operative approach to this recipient site.Methods A retrospective review was performed of all patients who underwent free tissue transfers to the medial sural vessels between December 2012 and December 2015 at a single institution. Preoperative imaging, operative approach, and technique for microvascular free tissue transfer to the medial sural vessels were reviewed. Postoperative results and complications were also analyzed.Results Using preoperative magnetic resonance angiography (MRA) to image the medial sural vessels and a retrograde perforator dissection technique, we successfully performed free tissue transfer to the distal medial sural vessels in 20 of 21 patients, representing the largest series reported. Postoperatively, 13 of 21 patients underwent MRA with a patent vascular pedicle demonstrated in all. There were no postoperative complications or resultant morbidities.Conclusion Surgeons should be aware of the medial sural vessels as a valuable recipient option for free tissue transfer to the lower extremity.
Keywords: medial sural; free tissue transfer; medial sural recipient